2021
DOI: 10.3390/agronomy11122409
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Rice Husk Biochar with Poultry Litter Co-Composts in Oxisols for Improving Soil Physico-Chemical Properties and Enhancing Maize Performance

Abstract: Efficient use of co-composted organic manure with biochar is one of the sustainable management practices in an agriculture system to increase soil fertility and crop yield. The objectives of this research are to evaluate the use of co-composted biochar, biochar in formulation with poultry litter (PL), and PL compost on soil properties and maize growth. Organic amendments were applied at 10 Mg ha−1, and synthetic fertilizer was applied at the recommended rate of maize (N: P2O5: K2O at 60:60:40 kg ha−1). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…The chemical speciation of metals in soil also influences their bioavailability and uptake by plants. Studies have shown that plants can readily absorb more soluble forms of metals, such as Cd and Pb, compared to less soluble forms (Kabata-Pendias & Mukherjee, 2007;Tandy et al, 2011;Alloway, 2013;Liu, 2013;Alarefee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical speciation of metals in soil also influences their bioavailability and uptake by plants. Studies have shown that plants can readily absorb more soluble forms of metals, such as Cd and Pb, compared to less soluble forms (Kabata-Pendias & Mukherjee, 2007;Tandy et al, 2011;Alloway, 2013;Liu, 2013;Alarefee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Table (3) the reason of significant differences between the earliest days to 50% silking and tasseling from interaction treatment of (poultry manure added with a level of 56 ton ha -1 a5b5). This could be due to increase in nutrient availability in rhizosphere, which can easily be accessed by plant roots then enhance plant growth (Alarefee et al, 2021). Table (4) the highest ear length was recorded by poultry manure (a5) compared to control (a1), this may be due to high nutrient content of poultry manure that contains of 1.52 and 7.28% of P and N respectively (table 10) which causes an increase in sweet corn growth as well as increase productivity(Abbas Mohammed et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Foliar concentrations analyses were conducted following Alarefee et al (2021). The leaves samples were cleaned with tap water and rinsed a few times with distilled water to remove adhering materials.…”
Section: Plant Analysismentioning
confidence: 99%